Control of oral infection using ozoniotherapy: literature review (Research, Society and Development, 2022)
The present work aims to review the literature and clarify the biological relevance of ozone therapy, involved in tissue restoration and its medicinal potential in the prevention, control and treatment of infections.With a great antimicrobial potential and a great biocompatibility, ozone is very indicated for fighting inflammation and infections in the oral cavity. A low-cost and quite reliable treatment for the preparation of this study was developed based on a survey in the PubMed database, on the Capes/Mec Periodicals Portal and on the Google Scholar database. Some articles were found which fit in theincorporation criteria. Lots of sources claimed  improvement of infections in the oral region after the administering of allotrope of oxygen (O2), ozone (O3). In association with medicines, this treatment can contribute to the improvement of the patient's life, by becoming a great therapeutic option.